Serosurveillance of Infectious Bovine Rhinotracheitis in Buffaloes in Baghdad governorate - Shakir Frayyeh Nezzal; Ibtesam Qasim Hassan (Mirror of Research in Veterinary Sciences and Animals, 2017)
Infectious Bovine Rhinotracheitis (IBR) is a greatly infectious contagious disease. It is caused by the Bovine herpesvirus (BHV-1) that affected both young and adult cattle. This study was designed to determine the serosurveillances of infectious bovine rhinotracheitis in buffaloes in Baghdad province. A totally, 125 serum samples were randomly collected from buffaloes of different ages and genders during July to December/ 2016 from various regions of Baghdad. All serum samples were tested using indirect ELISA. Totally, there were 51 (40.80%) positive serum samples, while, 74 (59.20%) were seronegative for IBR. The seropositive percentages in different locations in Baghdad were ranged from 20% to 51.66% in buffaloes. The highest seropositive cases were found in the age group less than 1-2 years old (48.93%) with high seropositivity in females with percentage of 41.34%. The highest seropositivity, were occurred in autumn and winter than summer months. Moreover, higher seropositive percentage (57.14%) was recorded in December, whereas, the lowest percentage was in July (20 %). A significant difference (P< 0.01) was observed in infected buffalo between the winter month’s season and months of other seasons. In conclusion, this study reported the diagnosis of BHV1 in buffaloes in Baghdad by indirect ELISA. Moreover, a widespread of the disease in different locations and different clinical forms were reported. The IBR infection appeared to be increased with the presence of environmental risk factors such as cold months and the high density of animals' population.